2010
DOI: 10.1007/s12640-010-9191-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Indicators of Clinical High-Risk States for Psychosis: A Critical Review of the Evidence

Abstract: The present review investigates the empirical evidence from cross-sectional and long-term follow-up studies on neurocognitive indicators of an increased risk for developing schizophrenia spectrum psychoses in clinically defined high-risk samples. First, the investigations at the Cologne center for early recognition and intervention are briefly summarized and then integrated within the available literature. Thirty-two studies with original data could be identified by extensive literature search. Cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 56 publications
4
32
1
Order By: Relevance
“…The aim of differentiating the depersonalization experience in the transitional area between psychosis and nonpsychosis is to more clearly determine differential diagnostic boundaries and to deliver new impulses for expanding the limits of early diagnostics [98,99]. An expectation which was formulated by Andreasen [100] in connection with the continued development of psychopathology has thus been met: ‘Fortunately, the Europeans still have a proud tradition of clinical research and descriptive psychopathology.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of differentiating the depersonalization experience in the transitional area between psychosis and nonpsychosis is to more clearly determine differential diagnostic boundaries and to deliver new impulses for expanding the limits of early diagnostics [98,99]. An expectation which was formulated by Andreasen [100] in connection with the continued development of psychopathology has thus been met: ‘Fortunately, the Europeans still have a proud tradition of clinical research and descriptive psychopathology.…”
Section: Resultsmentioning
confidence: 99%
“…Pennington and Ozonoff point to a discriminant validity problem common to many neuropsychological tests, whereby symptomatically different behavioral disorders present with similar neuropsychological deficits [100]. For example, executive function impairments were found in nearly every anxiety disorder [153], as well as in eating disorders [154], bipolar disorder [155], major depressive disorder [156], post-traumatic stress disorder [89], schizophrenia [157], antisocial personality disorder [158] and borderline personality disorder [159].…”
Section: Review Abramovitch Mittelman Henin and Gellermentioning
confidence: 99%
“…Chan et al (2009) observed some associations between some sustained attention assessment and schizotypal traits but no significant relationship between this assessment and clinical symptoms in patients with schizophrenia in this study; observations critical to the requirements of clinical staging in psychosis. Pukrop and Klosterkötter (2010) examined the risk situation for developing schizophrenia spectrum psychoses, of clinically defined high-risk subjects within an ''At Risk Mental State'' (ARMS). These patients were identified by the Cologne Early Recognition and Intervention Center, with regard to genetic, epidemiologic, and clinical high-risk studies on first-episode and multiple episode patients.…”
Section: Staging In Schizophreniamentioning
confidence: 99%